Development of advanced NO[sub x] control concepts for coal-fired utility boilers - Evans, A.; Pont, J. N.; England, G.; Seeker, W. R. (Energy and Environmental Research Corporation, 1993)
The complete CombiNO[sub x], process has now been demonstrated at a level that is believed to be representative of a full-scale boiler in terms of mixing capabilities. A summary of the results is displayedin Figure 5-1. While firing Illinois Coal on the Reburn Tower, Advanced Reburning was capable of reducing NO[sub x], by 83 percent. The injection of methanol oxidized 50--58 percent of the existing NO to N0[sub 2]. Assuming that 85 percent of the newly formed N0[sub 2] can be scrubbed in a liquor modified wet-limestone scrubber, the CombiNO[sub x], process has been shown capable of reducing NO[sub 2], by 90--91 percent in a large pilot-scale coal-fired furnace. There is still uncertainty regarding the fate of the N0[sub 2] formed with methanol injection. Tests should be conducted to determine whether the reconversion is thermodynamic or catalytic, and what steps can be taken (such as quench rate) to prevent it from happening.